Cores e sabores - Honorato, Pamela Daiane; Fernandes , Maria José; Paiva , Solange Fernandes; Andrade, Izandra Soares de; Carraro, Marcia Regina Simpioni (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2023)
>>> ver pdf